2017
DOI: 10.1053/j.gastro.2016.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Isocaloric Diets High in Animal or Plant Protein Reduce Liver Fat and Inflammation in Individuals With Type 2 Diabetes

Abstract: In a prospective study of patients with type 2 diabetes, we found diets high in protein (either animal or plant) significantly reduced liver fat independently of body weight, and reduced markers of insulin resistance and hepatic necroinflammation. The diets appear to mediate these changes via lipolytic and lipogenic pathways in adipose tissue. Negative effects of BCAA or methionine were not detectable. FGF21 level appears to be a marker of metabolic improvement. ClinicalTrials.gov ID NCT02402985.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
217
1
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 221 publications
(242 citation statements)
references
References 63 publications
12
217
1
12
Order By: Relevance
“…Another recent study suggested a beneficial effect of protein. This was an intervention study in 37 diabetics with mild steatosis (<30% lipid content on MRI), in whom intrahepatic lipid content reduced on a strict high vegetable or animal protein diet for 6 weeks 38. Since this study differs from ours in various ways (ie, our study included n=3882 individuals with a low prevalence of diabetes (13%) in an observational rather than an interventional study design with an outcome defined by >30% steatosis as set by the detection limits of ultrasonography), direct comparison is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study suggested a beneficial effect of protein. This was an intervention study in 37 diabetics with mild steatosis (<30% lipid content on MRI), in whom intrahepatic lipid content reduced on a strict high vegetable or animal protein diet for 6 weeks 38. Since this study differs from ours in various ways (ie, our study included n=3882 individuals with a low prevalence of diabetes (13%) in an observational rather than an interventional study design with an outcome defined by >30% steatosis as set by the detection limits of ultrasonography), direct comparison is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Again, with both high-protein diets, free amino acid concentrations were unchanged after the diet, but the animal-protein diet was associated with higher postprandial concentrations of BCAAs and methionine, suggestive of increased amino acid catabolism in skeletal muscle and liver (88). Both high-protein diets also significantly decreased serum concentrations of fibroblast growth factor 21 (FGF21) and decreased FGF21 receptor cofactor klotho b expression in adipose tissue (88). Elevated FGF21 is associated with NAFLD and is positively correlated with intrahepatic TG content (89,90).…”
mentioning
confidence: 91%
“…Both groups had decreased BMI, visceral adipose tissue, liver enzymes, plasma FFAs, and insulin and glucose concentrations (88). Again, with both high-protein diets, free amino acid concentrations were unchanged after the diet, but the animal-protein diet was associated with higher postprandial concentrations of BCAAs and methionine, suggestive of increased amino acid catabolism in skeletal muscle and liver (88). Both high-protein diets also significantly decreased serum concentrations of fibroblast growth factor 21 (FGF21) and decreased FGF21 receptor cofactor klotho b expression in adipose tissue (88).…”
mentioning
confidence: 95%
See 2 more Smart Citations